Effects of Bone Morphogenetic Protein‐7 on Steroid‐Induced Extracellular Matrix Accumulation in Human Trabecular Meshwork Cells - Eun Woo Kim; Jin‐Ok Choi; Min Kyung Chae; Jin‐Sol Lee; Chang Ha Lee; Jo Eun Um; Nam Hee Kim; Jihyeong Kim; Wungrak Choi; Chan Yun Kim (FASEB BioAdvances)
ABSTRACT Long‐term steroid use, though essential for treating eye diseases, can cause increased intraocular pressure (IOP) in susceptible individuals and may lead to steroid‐induced glaucoma in a subset of patients. This study investigated the effect of bone morphogenetic protein‐7 (BMP‐7) on steroid‐induced extracellular matrix (ECM) synthesis in human trabecular meshwork (TM) cells. We sought to explore the potential of BMP‐7 as a protective agent against steroid‐induced ECM accumulation in the TM. Human TM cells (HTMCs) were treated with either steroids alone or a combination of steroids and BMP‐7 to compare their effects on ECM production. BMP‐7, known for its transforming growth factor beta (TGF‐β) antagonistic properties, was administered using a micellized protein transduction domain (mPTD)‐fused BMP‐7 polypeptide to enhance activity. Gene expression analysis was conducted to identify specific genes involved in ECM regulation. BMP‐7 effectively inhibited steroid‐induced ECM accumulation in HTMCs. There was a significant reduction in ECM production in the steroid and BMP‐7 co‐treated group compared with that in the steroid‐only group. Furthermore, several genes involved in ECM regulation were identified in the co‐treatment, underscoring BMP‐7's potential role in modulating ECM metabolism. These findings demonstrate that BMP‐7 exerts protective, anti‐fibrotic effects in HTMCs by inhibiting steroid‐induced ECM synthesis. BMP‐7 may serve as a promising therapeutic target for preventing or treating steroid‐induced glaucoma by maintaining normal aqueous humor outflow and preventing IOP elevation.